Healthy Eating Index, Genomics and Metabolomics; Insights into the Mechanisms Driving Dietary Pattern to Metabolic Disorders. (29th May 2020) - Bagheri, Minoo; Shah, Rachana D; Mosley, Jonathan D; Ferguson, Jane F
Abstract: Objectives: Higher diet quality measured by healthy eating index (HEI) is associated with improved metabolic function, however the molecular basis remains unclear. We assessed associations between HEI and the metabolome in plasma and stool and explored interaction between genotype and HEI on circulating and gut metabolites. Methods: We analyzed data from heathy individuals recruited to a single cross-sectional study visit (ABO Study, N = 75). HEI score was calculated from food frequency questionnaire. Metabolites in plasma (n = 800) and stool (n = 767) were measured at Metabolon Inc. Genotyping was performed by Exome chip (Illumina, CoreExome, N > 540, 000 variants). Multivariable linear regression was used to assess the association of HEI score with metabolites adjusting for age, sex and body mass index. Plasma associations were replicated in the Fish oils and Adipose Inflammation Reduction (FAIR) study (N = 29). Metaboanalyst 4.0 was used to determine metabolic pathways. The interaction of single nucleotide polymorphisms (SNPs) and HEI on metabolites was tested using Plink. Results: Metabolites in plasma (n = 74) and stool (n = 77) were associated with the HEI index ( P  < 0.05). One metabolite (N-acetyl-beta-alanine) overlapped between plasma (B = 0.003, P  = 0.035) and stool (B = 0.008, P  = 0.02). Glycine replicated between ABO (B = −0.001, P  = 0.02) and FAIR studies (B = −0.01, P  = 0.02). In plasma there was significant pathway enrichment in glycerophospholipid metabolism, glycine, serine-threonine metabolism and caffeine metabolism. In stool, histidine and caffeine metabolism pathways were significantly enriched. Significant (Pinteraction <5 × 10−8) interactions were observed between HEI and multiple independent SNPs for metabolites including circulating Valylleucine and gut Sedoheptulose-7-phosphate. Conclusions: Diet quality, measured by HEI, is associated with differences in plasma and stool metabolites. The observed associations might aid understanding the link between food patterns and metabolic health outcomes. Further, our data support gene-nutrient interactions between HEI and SNPs contributing to plasma and gut metabolomic profiles. Future work will explore the relationship between HEI and gut microbiome composition. Funding Sources: This project was supported by the National Institutes of Health.